The Effect of Empowering Education Combined With Mindfulness Meditation Training on Negative Emotion and Quality of Life in Patients With Inflammatory Bowel Disease - Xi, Wei-Zhen; Xu, Chong-Wu; Wang, Ling-Ling (Frontiers in Behavioral Neuroscience, 2022)
Objective To investigate the effect of empowerment education combined with mindfulness meditation training on negative emotions and quality of life in patients with inflammatory bowel disease (IBD). Methods A total of 40 patients with IBD were selected and divided into experimental group and control group according to the random number table method, 20 cases in each group. The patients in the control group were treated with conventional nursing methods. The patients in the experimental group used empowerment education combined with mindfulness meditation training. Changes in mood and quality of life were compared between the two groups at admission and 3 months after discharge. Results There was no significant difference in SAS score and quality of life score between the two groups. After authorization education combined with mindfulness meditation training, the SAS score of the experimental group was significantly lower than that of the control group (P < 0.01). The score of quality of life in the experimental group was significantly higher than that in the control group (P < 0.01). Conclusion Empowerment education combined with mindfulness meditation can effectively improve the negative emotions and quality of life of patients with inflammatory bowel disease, and benefit the patients in many aspects.